Effect of sucralose and biostimulant on pre-and postharvest of blueberries (Vaccinium corymbosum L. cv. Elliot ) under organic and conventional production systems (2016)
Blueberries (Vaccinium corymbosum L. cv. Elliot) from organic and conventional sources were subjected to either a pre-harvest application with an organic biostimulant or a post-harvest coverage with sucralose. Fruits were assessed in terms of firmness, dry matter, ascorbic acid, soluble solids, sensory attributes and color, during storage at 0 °C and RH of 90%, for a period of 21 days. Each trial with three treatments: T0correspondingto the control, T1to an application of biostimulant,22 days before harvest, and T2 to a post-harvest coverage with sucralose. Fruits were evaluated in sensory aspect, with the participation of thirteen panelists, on day fifteen after being harvested and stored. Evaluations of both maturity and quality parameters were performed on days 1,7, 14and 21post-harvest.Pre-harvest treatment with the organic biostimulant showed a higher variation in dry matter and soluble solids, but these variations are not significant. The group with a coverage of Sucralose showed a significant increase in fruit firmness. The best sensory evaluation, was given by the panelists to the organic farming. Fruit measurements, such as color, ascorbic acid and colorimetry showed no significant differences in the results.